PENGARUH AROMATERAPI BUNGA LAVENDER (Lavandula angustifolia) TERHADAP INTENSITAS NYERI HAID (DISMENORE) PADA MAHASISWI STIKES MADANI YOGYAKARTA - yuliana Vivian Maharani; fatmawati, ery; rahmah widyaningrum (Jurnal Kesehatan Madani Medika (JKMM), 2016)
Dysmenorrhea or painful menstruation is one of the most common gynecological problems experienced by women of all ages. Lavender fragnance therapy is used for pain treatment, for reducing pain post-caesarean section, reducing depression and anxiety in postpartum and reducing dysmenorrhea. The research is to identify effects of lavender fragnance therapy (Lavandula angustifolia) to overcome pain intensity during mentruation (dysmenorheal) case study the students of STIKes Madani Yogyakarta. This study is a quantitative research with quasi experimental approach. Purposive sampling technique is used in this study. The paired t-test is used for statistical test to analyze the effectiveness of lavender fragnance to overcome dysmenorrhea pain intensity. Most respondents according to the age are between 18-20 years old, which is 60%. Most characteristic dysmenorrhea pain prior to administration of lavender fragnance therapy was a moderate pain scale with intensity of 65%. Meanwhile, after giving lavender fragnance therapy the highest intensity of pain was mild pain scale with intensity of 75%. There were significant effect of lavender fragnance therapy on reducing the dysmenorrhea pain intensity.